2003
DOI: 10.1029/2003gl017425
|View full text |Cite
|
Sign up to set email alerts
|

A 2,326‐year tree‐ring record of climate variability on the northeastern Qinghai‐Tibetan Plateau

Abstract: [1] High-resolution climate proxy records covering the last two millennia on the Qinghai-Tibetan Plateau are scarce yet essential to evaluation of the patterns, synchroneity and spatial extent of past climatic changes including those in the Medieval Warm Period (MWP) and the Little Ice Age (LIA). Here we present a 2326-year tree-ring chronology of Sabina przewalskii Kom. for Dulan area of northeastern Qinghai-Tibetan Plateau. We find that the annual growth rings mainly reflect variations in regional spring pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
227
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 320 publications
(254 citation statements)
references
References 17 publications
22
227
3
2
Order By: Relevance
“…Among the 11 sites, only DLH6 yielded cores less than 1000 years in length, and the longest sample was obtained at DLH3 going back to 404 AD. We compared our chronologies with an archaeological ring-width chronology and the Dulan chronology (Zhang et al, 2003a;Kang et al, 1997;Tarasov et al, 2003; , 2004). The comparisom revealed that dating trees from the arid and semi-arid regions can be very difficult because of the missing rings and replications and comparisons between chronologies are extremely beneficial to improve the accuracy of chronologies.…”
Section: Developing Ring-width Chronologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 11 sites, only DLH6 yielded cores less than 1000 years in length, and the longest sample was obtained at DLH3 going back to 404 AD. We compared our chronologies with an archaeological ring-width chronology and the Dulan chronology (Zhang et al, 2003a;Kang et al, 1997;Tarasov et al, 2003; , 2004). The comparisom revealed that dating trees from the arid and semi-arid regions can be very difficult because of the missing rings and replications and comparisons between chronologies are extremely beneficial to improve the accuracy of chronologies.…”
Section: Developing Ring-width Chronologiesmentioning
confidence: 99%
“…Since 1998, 1050 tree-ring increment cores have been extracted from 493 living trees at Zongwulong, Shalike and Qinghai Nanshan mountains (Figure 1) in the northeastern part of Qaidam Basin. The 11 sampling sites (DLH1-6, TJ1, and WL1-4) are located to the north of the Dulan Chronology site (Zhang et al, 2003a;Tarasov et al, 2003). Table I presents the details of these sites and the sample depths.…”
Section: Study Area and The Tree-ring Sampling Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrumental measurement is sparse and short-term in southwestern China, but climatic conditions can be extended back several centuries with high-resolution climatic proxies. Tree-ring records are widely used as climatic proxies, because they provide annual resolution, precise dating and adequate duplicate data and have been proven to be an efficient proxy for past climate reconstruction [1][2][3][4][5].…”
mentioning
confidence: 99%
“…In addition to modern geographical processes, studies on historical geographical progresses also made prominent achievements. In those studies, a large number of archives were used to retrieve the environmental evolution, including ice cores (Yao et al, 1997;Shi et al, 1999b), loess Liu et al, 1998), sporopollen (Song et al, 1999), speleothems (Wang et al, 2005b;Zhang et al, 2008c), tree rings (Zhang et al, 2003;Li et al, 2006) and historical documentary data (Chu, 1973;Ge et al, 2003). Some of the studies even reached an international advanced level.…”
Section: Land Surface Geographical Processesmentioning
confidence: 99%